Analysis of parental behaviour and attitude in sports and its relation with the sports performance - Sánchez-Romero, E. I.; Ponseti-Verdaguer, F. J.; Pulido, D.; Borràs, P. A. (Journal of Human Sport & Exercise, 2020)
The aim of the present investigation was to analyse the relation between parental behaviour and other socio-demographic and sportive variables with their children`s sports performance. A sample of 223 parents (46.2% men; 53.4% women) of 223 youth athletes (77.13% boys; 22.87% girls; Mage = 11.66 years; DE = 1.60) were asked. All of them belonged to 13 grassroots teams: football (soccer) (48.9%), basketball (13.5%), volleyball (34.1%) and handball (3.6%) of different categories: U-12 (36.8%), U-13 (48%) and U-15 (15.2%). A retrospective ex post facto design of unique group was planned. The questionnaire Análisis del Comportamiento y Actuación de los Padres y Madres en el Deporte (ACAPMD) was used. Differences statistically significant were detected between parental behaviour to the sports, socio-demographic variables (age and athlete`s gender, parents` gender and geographical zone) and sports variables (sports category and sport played) with the sports performance. An age increase above the mean, it will make more probable a high sports performance. The clubs of out of Palma registered the highest percentage of sports performance and low sports performance. The highest percentage of high performance was registered in men and women highlighted in medium and low performance. The highest percentages of high and medium performance were registered when the mothers answered the questionnaire. The highest percentage of high and low performance was registered in basketball. And, the highest percentage of sports performance was in U-12`s category, U-13`s category highlighted in low performance and U-15`s category highlighted in medium performance.